1977
DOI: 10.1079/bjn19770108
|View full text |Cite
|
Sign up to set email alerts
|

Rates of rumen fermentation in relation to ammonia concentration

Abstract: 1. Four sheep were fed from automatic continuous feeders on whole barley fortified with graded levels of a urea solution. This approach was to a large extent successful in maintaining relatively steady states of rumen ammonia concentration.2. Rates of barley fermentation in the rumen at various rumen NHI concentrations were assessed by measuring the disappearance of barley dry matter from polyester bags suspended in the rumen of these sheep.3. The minimal NH:, concentration for maximal rate of fermentation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
130
3
45

Year Published

1979
1979
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(191 citation statements)
references
References 9 publications
(4 reference statements)
13
130
3
45
Order By: Relevance
“…A low energy content will also limit the utilisation of non-protein nitrogen (NPN) in the rumen for providing microbial protein (MP) to the animal (Satter & Roffler 1977), resulting in an accumulation of ammonia in the rumen (Leng 1990). On the other hand, sufficient protein is essential to provide ammonia-nitrogen (NH3-N) for normal microbial growth (Satter & Slyter 1974) and optimal rumen fermentation (Mehrez et al 1977). In the case of low NH3-N concentration, both MP production and intake may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A low energy content will also limit the utilisation of non-protein nitrogen (NPN) in the rumen for providing microbial protein (MP) to the animal (Satter & Roffler 1977), resulting in an accumulation of ammonia in the rumen (Leng 1990). On the other hand, sufficient protein is essential to provide ammonia-nitrogen (NH3-N) for normal microbial growth (Satter & Slyter 1974) and optimal rumen fermentation (Mehrez et al 1977). In the case of low NH3-N concentration, both MP production and intake may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, estes valores estariam sempre aquém daqueles considerados ótimos (23,5 mg/100 mL) por Mehrez et al (1977) em vacas de alta produção, para se atingir o máximo em fermentação microbiana.…”
Section: Resultsunclassified
“…Esses parâmetros cinéticos são importantes porque eles não só descrevem a digestão, mas também caracterizam as propriedades intrínsecas dos alimentos que limitam sua disponibilidade aos ruminantes (Mertens, 1993). De acordo com Mehrez et al (1977), os modelos semi-logarítmicos ou exponenciais são apropriados para o estudo da degradação das forrageiras. Orskov & McDonald (1979) sugeriram um modelo exponencial para auxiliar no estudo da degradação de forrageiras no rúmen e uma equação baseada no princípio de redução do material durante a incubação, no estudo da degradação em função do tempo de incubação no rúmen.…”
Section: R Bras Zootec V31 N1 P148-156 2002unclassified
“…The evidence indicated that there was a metabolic adaptation in the rumen for better utilization of ammonia. Concentrations of amino acids and peptides were nearly 1 mM in the rumen fluid throughout the day and increased to 3 Roffler and Satter (1975a,b) did not always correctly predict lactation response in cattle fed urea or ammonlatreated corn silage (Huber 1975 (Mehrez et al 1977) is higher than the 5 mg/tOO mL suggested by Satter and Slyter (1914 …”
mentioning
confidence: 82%